The Motor Imagery (MI) Intervention and Rubber Ball Grafting Therapy on Rehabilitation and Increasing Motor Strength in Stroke Patients: Literature Review - Zahroh, Chilyatiz; Septianingrum, Yurike; Zulkarnain, Eva Vera (Journal of Applied Nursing and Health, 2024)
Background: Strokes are A disease caused narrowing of the vessels blood to the brain, which can obstruct Genre blood and also oxygen to the brain, and also can stop. Objective from the literature review This is For now influence motor imagery (MI) intervention and therapy holding a rubber ball to rehabilitation and improvement strength motor skills in stroke patients .Methods: Article methodology This is a literature review that searched the following databases: Science Direct, PubMed, and Google Scholar for articles published between 2019 and 2024 that dealt with the following topics: motor imagery (MI), therapy involving a rubber ball, rehabilitation after a stroke, motor strength, and stroke.   Results: From the results of identification based on inclusion criteria and review of eligibility, 10 articles were obtained for review . Studies literature review obtained results that There is influence motor imagery (MI) intervention and therapy holding a rubber ball to rehabilitation and improvement strength motor skills in stroke patients . Conclusion: The Motor Imagery (MI) Intervention and Rubber Ball Grafting Therapy may be recommended for patients who have muscle strength problems in stroke patients in rehabilitation centers.